Design of a New [PSI+]-No-More Mutation in SUP35 With Strong Inhibitory Effect on the [PSI+] Prion Propagation - Danilov, Lavrentii G.; Matveenko, Andrew G.; Ryzhkova, Varvara E.; Belousov, Mikhail V.; Poleshchuk, Olga I.; Likholetova, Daria V.; Sokolov, Petr A.; Kasyanenko, Nina A.; Kajava, Andrey V.; Zhouravleva, Galina A.; Bondarev, Stanislav A. (Frontiers in Molecular Neuroscience, 2019)
A number of [PSI + ]-no-more (PNM) mutations, eliminating [PSI + ] prion, were previously described in SUP35. In this study, we designed and analyzed a new PNM mutation based on the parallel in-register β-structure of Sup35 prion fibrils suggested by the known experimental data. In such an arrangement, substitution of non-charged residues by charged ones may destabilize the fibril structure. We introduced Q33K/A34K amino acid substitutions into the Sup35 protein, corresponding allele was called sup35-M0. The mutagenized residues were chosen based on ArchCandy in silico prediction of high inhibitory effect on the amyloidogenic potential of Sup35. The experiments confirmed that Sup35-M0 leads to the elimination of [PSI + ] with high efficiency. Our data suggested that the elimination of the [PSI + ] prion is associated with the decreased aggregation properties of the protein. The new mutation can induce the prion with very low efficiency and is able to propagate only weak [PSI + ] prion variants. We also showed that Sup35-M0 protein co-aggregates with the wild-type Sup35 in vitro and in vivo. Moreover, our data confirmed the utility of the strategy of substitution of non-charged residues by charged ones to design new mutations to inhibit a prion formation.